Fabrication and application of electrically conducting composites for electromagnetic interference shielding of remotely piloted aircraft systems. (15th January 2020) - Turczyn, Roman; Krukiewicz, Katarzyna; Katunin, Andrzej; Sroka, Jan; Sul, Przemysław
Abstract: Electromagnetic interference (EMI) is the phenomenon occurring in remotely piloted aircraft systems, especially in the radio-frequency band emitted by motors and power supplies, that needs to be shielded in order to avoid disturbances in communication signals. This paper presents a solution to this problem in the form of EMI shielding housing based on electrically conducting epoxy resins filled with polyaniline (PANI) and polypyrrole (PPy). For this purpose, PANI and PPy were synthesized and characterized to achieve effective EMI shielding of the resulting composite materials and reinforced with carbon fabric. Optimized materials were then used as EMI shielding housing for a remotely piloted aircraft system. The obtained results of electromagnetic compatibility tests showed the ability of damping of both manufactured composites, especially in the range of 30–35 MHz, where damping was the highest, with the average difference between conducting and non-conducting composites of ca. 20 dBµV/m.